Economic burden and quality of life caused by non-hodgkin lymphoma cancer in Iran - Marzieh Ghiasi; Hossein-Ali Nikbakht; Amirmohammad Tajik; Vahid Ghavami; Roham Salek; Mahboubeh Darabi; Sahar Mohammadnabizadeh; Seyyed Morteza Mojtabaeian; Farshad Sharifi; Mehdi Varmaghani (Journal of Health, Population and Nutrition)
Abstract Introduction Non-Hodgkin’s lymphoma (NHL) poses significant clinical and economic challenges in Iran, where rising cancer rates strain healthcare systems and compromise patient quality of life. This study assesses the direct and indirect costs associated with NHL and their impact on patient well-being. Methods A cross-sectional, descriptive-analytical study was conducted over a six-month period at Omid Hospital in Mashhad, Iran. Data were collected through face-to-face interviews with 83 NHL patients using validated questionnaires adapted to capture detailed information on direct medical and non-medical expenses, as well as productivity losses. Quality of life (QOL) was assessed via the EQ-5D and EORTC QLQ-C30 instruments. Statistical analyses, including regression models performed in STATA, were employed to examine associations between disease stage, costs, and QOL. Results Direct treatment costs by stage were $1,078.11 ± $631.45 (stage 1), $583.40 ± $289.73 (stage 2), $810.42 ± $324.46 (stage 3), and $662.59 ± $361.70 (stage 4). Indirect costs were $56.72 ± $7.36 (stage 1), $82.80 ± $21.39 (stage 2), $105.15 ± $24.02 (stage 3), and $116.32 ± $34.92 (stage 4), totaling $1,334.63 ± $711.56 (stage 1), $1,161.43 ± $494.97 (stage 2), $1,297.07 ± $337.16 (stage 3), and $1,119.32 ± $457.27 (stage 4). EQ-5D scores fell from 0.63 ± 0.23 (stage 1) to 0.43 ± 0.29 (stage 4) at baseline, reflecting similar trends after six months. These results suggest that overall QOL, as measured by QOL, tends to decrease as the disease progresses from stage 1 to stage 4. However, there may be some variations in QOL changes between different stages. Conclusion These findings underscore the substantial economic burden of NHL and its adverse impact on patient quality of life in Iran. Early diagnosis, improved access to specialized cancer centers, and increased financial support are crucial for enhancing health outcomes for NHL patients. Implementing these studies can improve patient access to care and boost overall health outcomes in society.